(untitled) (American Journal of Interdisciplinary Research and Innovation, 2024)
Ethnicity detection, or the automatic determination of people’s ethnic backgrounds using visual data, has become important in a number of disciplines, including social sciences, demographics, and computer vision. With a focus on Bangladesh’s complex cultural landscape, we describe in this paper a novel method for ethnicity detection using convolutional neural networks (CNNs). We gathered a dataset of photographs depicting members of the three main ethnic groups living in the Chittagong hill neighborhood: Chakma, Marma, and Tripura. Utilizing the DenseNet121 model’s robust feature extraction skills, we customized the architecture to meet the needs of our particular ethnicity detection application. A wide range of performance indicators were used to train and assess our unique CNN model. The outcomes illustrate accurate ethnicity detection technology’s potential for identifying and resolving social inequities while showcasing a promising level of accuracy. To address possible biases in the model’s prediction, ethical considerations are also covered. Overall, this work advances knowledge of Bangladesh’s ethnic variety and demonstrates the potential of CNNs for ethnicity detection. The results provide up new avenues for investigation and applications that advance a more diverse and inclusive society.